State somatic and motor skills Children with Kindergarten Public Cekcyn - Kuźniewska, Ewa; Napierała, Marek; Pezala, Małgorzata; Gotowski, Rafał (Journal of Education, Health and Sport, 2016)
The aim of the study was to determine the state of somatic and motor skills of children from Kindergarten Public Cekcyn. For this purpose, measurements height, weight and Sekity test was conducted Wroclaw. The resulting research material allowed to determine the degree of physical fitness among girls and boys aged 4, 5 and 6 years old. Conclusions: (1) Children from Kindergarten Public Cekcyn characterized by athletic build, (2) The boys have a better physical fitness than girls of the same age in most trias, (3) Comparison own research results to the results of research from Szczecin confirmed the superior level of the children from the urban environment.